What Makes a Currency Procyclical? An Empirical Investigation - Cordella, Tito (World Bank Group, Washington, DC, 2014)
This paper looks at the correlation between the cyclical components of gross domestic product and the exchange rate and classifies countries' currencies as procyclical if they appreciate in good times, countercyclical if they appreciate in bad times, and acyclical otherwise. With this classification, the paper shows that: (i) the countries that are commodity exporters and experience procyclical capital flows tend to have procyclical currencies; (ii) countries with procyclical currencies tend to restrict their capital accounts, perhaps as an attempt to reduce the degree of procyclicality; (iii) countries with procyclical currencies pursue procyclical monetary policy; (iv) however, in the last decade, there is a disconnect between the cyclicality of currency and monetary policy; and (v) the disconnect may reflect a decline in the fear of floating, which can be partially attributed to an improvement in countries' net foreign asset positions.